2023
DOI: 10.3389/fnut.2023.1090338
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in non-alcoholic liver disease: Molecular mechanisms and therapeutic implications

Abstract: Ferroptosis refers to a novel modality of regulated cell death characterized by excessive iron accumulation and overwhelming lipid peroxidation, which takes an important part in multiple pathological processes associated with cell death. Considering the crucial roles of the liver in iron and lipid metabolism and its predisposition to oxidative insults, more and more studies have been conducted to explore the relationship between ferroptosis and various liver disorders, including non-alcoholic fatty liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…The first limitation is that the etiology of MASLD/ MASH-HCC remains largely unclear, and further research is still needed. Recent studies have shown that new mechanisms of regulated cell death, such as ferroptosis, can be involved in the development and progression of MASLD (Feng et al, 2022;Zhang et al, 2023b;Zou et al, 2023) to HCC (Cong et al, 2022;Wang et al, 2023a;Wang et al, 2023b;Xu et al, 2023), and modulating ferroptosis may be a potential novel therapeutic target for MASLD and HCC (Yin et al, 2022;Ajoolabady et al, 2023;Cheng et al, 2023). However, mechanistic details relating to ferroptosis and the molecular pathways concerning transition of MASLD to HCC have been lacking.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The first limitation is that the etiology of MASLD/ MASH-HCC remains largely unclear, and further research is still needed. Recent studies have shown that new mechanisms of regulated cell death, such as ferroptosis, can be involved in the development and progression of MASLD (Feng et al, 2022;Zhang et al, 2023b;Zou et al, 2023) to HCC (Cong et al, 2022;Wang et al, 2023a;Wang et al, 2023b;Xu et al, 2023), and modulating ferroptosis may be a potential novel therapeutic target for MASLD and HCC (Yin et al, 2022;Ajoolabady et al, 2023;Cheng et al, 2023). However, mechanistic details relating to ferroptosis and the molecular pathways concerning transition of MASLD to HCC have been lacking.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Duodenal cells that take up iron from the diet and reticuloendothelial macrophages that recover iron from aged erythrocytes are the main suppliers of blood iron, with others provided by body stores such as liver cells, cardiac myocytes, and erythroid cells [ 18 , 21 ]. Approximately one-third of iron is stored in the liver, which makes the liver potentially more sensitive to ferroptosis [ 22 ]. After aged erythrocytes are phagocytized by reticuloendothelial macrophages, heme is degraded by heme oxygenase-1 (HO-1), and inorganic iron is recovered [ 23 ].…”
Section: The Mechanisms Of Ferroptosismentioning
confidence: 99%
“…As an important ferroptosis regulator, NRF2 was shown to be down-regulated in NAFLD mice, and enhancing the NRF2/HO-1 pathway could effectively prevent the development of NAFLD [ 147 , 148 ]. Accumulating evidence suggests that ferroptosis can induce oxidative stress, aggravate inflammation, and promote cell damage, thereby accelerating the pathological process of NAFLD [ 22 ]. Given the close association between ferroptosis and NAFLD, exploring several potential NAC targeting ferroptosis to treat NAFLD is necessary.…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…However, the role of ferroptosis in the development and progression of liver diseases remains poorly explored [220]. A number of studies have shown that ferroptosis may be a novel type of cell death associated with liver diseases, such as viral hepatitis, drug-induced liver injury [221], alcoholic liver disease [222], non-alcoholic fatty liver disease (NAFLD) [223], non-alcoholic steatohepatitis (NASH) [224], and hemochromatosis [225]. Tsurusaki et al [224] identified the type of cell death that occurs at the earliest stage of NASH.…”
Section: Anti-ferroptosis and Anti-pyroptosis Effects Of Mscmentioning
confidence: 99%